(untitled) (Research, Society and Development, 2022)
Tuberculosis is among the leading causes of death in children. In addition, it is recognized that its occurrence is spatially dependent, with higher incidence/prevalence in regions of greater socioeconomic and programmatic vulnerability. Thus, the objective was to analyze the spatial distribution of tuberculosis cases in Brazil, between 2010 and 2020. An ecological study was carried out, in which tuberculosis notifications in children in the Brazilian state were analyzed. Data were collected in the Notifiable Diseases Information System, considering the year of diagnosis and the place of notification. Tuberculosis incidence coefficients in children aged 0 to 9 years were calculated. Furthermore, data were presented with absolute and relative frequency, as well as percentage variation between the beginning and the end of the period. For the spatial distribution, a choropleth map was constructed. Between 2010 and 2020, 14,802 cases of tuberculosis were recorded in children in Brazil, with an average coefficient of 4.5/100,000 inhabitants. The spatial distribution showed a higher concentration of cases in the states of the North and Southeast regions, as a possible consequence of programmatic and demographic aspects, respectively. There was a drop in cases in 2020, presumably because of the reorganization of health actions and services to combat COVID-19. In addition, between the beginning and the end of the series, different behaviors were observed in the country, with an increase in some states and a decrease in others. This scenario highlights the importance of ecological studies, as they provide the opportunity to identify the occurrence of diseases in different locations, aiming at subsidizing public policies to combat them.